Migranyan, A.M. Russia and the USA: Factor of Putin. Moscow: OOO «TD Algoritm», 2016. 272 p. (in Russian) (Сравнительная политика)
Migranyan, A.M. Russia and the USA: Factor of Putin. Moscow: OOO «TD Algoritm», 2016. 272 p. (in Russian).